Myrcia amplifolia (Myrtaceae), a new species from the Atlantic Forest of southern Bahia, Brazil - Fernandes, Thiago; Santos, Matheus Fortes; Braga, João Marcelo Alvarenga (Phytotaxa, 2020)
Myrcia amplifolia, a new species from the coastal forest of southern Bahia, eastern Brazil, is here described and compared with morphologically similar species. Additionally, a morphological plate, distribution map and conservation assessment of the species are presented. We assign the new species to Myrcia sect. Calyptranthes with a reasonable reliability due to the combination: presence of cataphylls, inflorescences sympodially branching at the base and calyptrate flowers. Myrcia amplifolia seems to be closely related to M. carioca, from which it can be distinguished through the leaf blades strongly coriaceous (vs. chartaceous in M. carioca), leaf venation very slightly raised and barely conspicuous abaxially (vs. venation strongly raised and conspicuous abaxially), inflorescences with a shorter main axis (75–110 mm long vs. 130–270 mm long), and shorter first lateral branch (3.3–19 mm long vs. 48–95 mm long), and the calyptra acuminate (vs. rounded or shortly apiculate). It is also similar to M. boanova, differing by the leaf blades significantly larger (31–60 × 10–20 cm vs. 7–13 × 4.1–5 cm in M. boanova) and strongly coriaceous (vs. chartaceous), and the calyptra acuminate (vs. rounded) and smaller (2.3–2.6 × ca. 1.8 mm vs. 3.5–3.7 × 3.5–4 mm).